2010
DOI: 10.1002/ajmg.a.33555
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying early development of pulmonary vascular obstructive disease in Down syndrome: An imbalance in biosynthesis of thromboxane A2 and prostacyclin

Abstract: Patients with Down syndrome (DS) and a left-to-right shunt often develop early severe pulmonary hypertension (PH) and pulmonary vascular obstructive disease (PVOD); the pathophysiological mechanisms underlying the development of these complications are yet to be determined. To investigate the mechanisms, we evaluated the biosynthesis of thromboxane (TX) A(2) and prostacyclin (PGI(2)) in four groups of infants, cross-classified as shown below, by measuring the urinary excretion levels of 11-dehydro-TXB(2) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…This is also consistent with previous studies that have documented reduced endothelium-dependent vasodilation in DS patients compared with age-matched healthy individuals [25] and an imbalance in the synthesis of the vasoconstrictor thromboxane A2 compared with the vasodilator prostacyclin in children with DS [10]. In addition, children with PAH-CHD and DS are less responsive to inhaled nitric oxide than children with PAH-CHD but without DS [26].…”
Section: Discussionsupporting
confidence: 91%
“…This is also consistent with previous studies that have documented reduced endothelium-dependent vasodilation in DS patients compared with age-matched healthy individuals [25] and an imbalance in the synthesis of the vasoconstrictor thromboxane A2 compared with the vasodilator prostacyclin in children with DS [10]. In addition, children with PAH-CHD and DS are less responsive to inhaled nitric oxide than children with PAH-CHD but without DS [26].…”
Section: Discussionsupporting
confidence: 91%
“…Some of the molecular factors that may cause PH in this population have been evaluated; however, the results have been mixed [6,10]. In this study, ADMA, a NO synthase inhibitor, was found to be significantly higher in DS patients with PH than in those DS patients without PH.…”
Section: Discussionmentioning
confidence: 55%
“…In persons with Down syndrome and CHD with a left-right shunt, there is an imbalance in vasoactive mediators which favours vasoconstriction, platelet aggregation and cell proliferation in the pulmonary vasculature [54]. Infants with Down syndrome have a high rate of PAH that is disproportionate for their age [55][56][57], and ∼30% of adults with Down syndrome have septal defects and higher associated mortality compared to those without Down syndrome [58].…”
Section: Respiratory Disease In Down Syndromementioning
confidence: 99%